2009
DOI: 10.1111/j.1443-1661.2009.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Look Colonoscopy: Indication and Requirements

Abstract: Finally, in most developed countries, a priority is attributed to screening of colorectal cancer and focus is given on quality assurance of colonoscopy which is considered as the gold standard procedure in the secondary prevention of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Colonoscopy as the gold standard procedure in the exploration of the large bowel is frequently used as the first investigation when there is any suspicion of lower gastrointestinal‐tract symptoms (Rey & Lambert 2009). According to Paspatis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy as the gold standard procedure in the exploration of the large bowel is frequently used as the first investigation when there is any suspicion of lower gastrointestinal‐tract symptoms (Rey & Lambert 2009). According to Paspatis et al.…”
Section: Introductionmentioning
confidence: 99%
“…We found that in over twothirds of our patients a second-look colonoscopy was performed because of an incomplete polypectomy or to examine the polypectomy scar for residual neoplastic tissue. According to literature data, a second-look colonoscopy for the control aft er polypectomy occurs in ∼ 1 or 2% of the procedures with endoscopic treatment and is usually limited to the previously treated area ( 19 ). Our results indicate a much higher rate of second-look colonoscopies.…”
Section: Discussionmentioning
confidence: 63%
“…As more screening programs are implemented worldwide, it becomes important to estimate the number of colonoscopies needed for CRC screening. To our knowledge, this is the fi rst study to evaluate the need for second-look colonoscopies, as previous literature has mainly focused on failed cecal intubation as a cause for a second colonoscopy ( 19,21,22 ). In our cohort, cecal intubation failed in 3% of the colonoscopies.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation